Religious Education in Azerbaijan - Mammadov, Jeyhun (Scholarya Demo Journal of Ruby, 2018)
The article discusses the history of religious education in Azerbaijan. It emphasizes the emergence of various madrasahs, growth of many famous personalities, and contributions of Azerbaijani scholars to Islamic culture since the spread of Islam in Azerbaijan. The author sheds light on the restriction of the activities of madrasahs after the occupation of Azerbaijan by tsarist Russia, their elimination and execution of religious scholars after the establishment of the Soviet Union. The article also mentions that religious educational centers were established in Bukhara (Uzbekistan), Samarkand (Uzbekistan), Kazan (Tatarstan) and other cities after the collapse of the Soviet Union, and Muslim population of the USSR including Azerbaijanis attended these centers to study religious sciences. It touches upon government’s care for religion and establishment of new educational institutions after Azerbaijan gained its independence.